The invisible victim in criminal policy - Kainulainen, Heini (Bergen journal of criminal law & criminal justice, 2021)
The ideology behind the Finnish criminal policy is described as humane and rational. In line with this policy, efforts are made to reduce the use of the criminal justice system to solve societal problems. One of the internationally celebrated landmarks of this policy is the success in keeping the imprisonment rate at a low level. , In this article we argue, that while this policy has been sensitive towards the needs of the offenders, it has failed to recognize the needs of victims, especially the vulnerabilities related to the victimisation of violence and sexual violence. International critical analyses on the appraisal of the victim rights have raised fears among the criminal policy planners in Finland and prevented analytical discussion. Furthermore, the reluctance to involve the victim perspective in the criminal political discussions is based on mistaken ideas of what the victims really want. In the article, we will consider how to strengthen the position of the victim without making the criminal policy more punitive in general.